PENGARUH INOVASI ORGANISASI, KNOWLEDGE MANAGEMENT, KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA PEGAWAI PADA DINAS LINGKUNGAN HIDUP KABUPATEN BUTON UTARA - Nindy Ade Marsalena; Alida Palilati; Yusuf Yusuf; Moh. Amin; Muh. Rivan Kohawan (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2020)
This research was conducted with the aim to determine the effect of organizational innovation partially significant on employee performance, to determine the effect of knowledge management partially significant influence on employee performance, to determine partially transformational leadership has a significant effect on employee performance and to determine the effect of organizational innovation, Knowledge management and transformational leadership simultaneously have a significant effect on employee performance at the Environmental Service Office of North Buton Regency. This study used 50 respondents as civil servants of the North Buton Regency Environmental Service. The sampling technique in this study was carried out by means of the census technique so that the entire population was used as the research sample. The research data were collected using interviews and questionnaires. The analysis technique uses multiple linear regression analysis with the help of SPSS software.The results of this study indicate that there is a positive and significant influence between organizational innovation partially on employee performance, knowledge management also has a partially significant positive effect on employee performance. Meanwhile, transformational leadership has a partially significant positive effect on employee performance. The same results were also found on the influence of organizational innovation, knowledge management, and transformational leadership simultaneously having a significant effect on employee performance at the North Buton Regency Environmental Service.